Mucocutaneous manifestations of COVID‐19‐related multisystem inflammatory syndrome in adults: an update. (1st October 2022) - Sil, Abheek; Das, Anupam; Datta, Debatri
Abstract: Multisystem inflammatory syndrome in adults (MIS‐A) is an inflammatory condition that affects multiple extrapulmonary organ systems (cardiac, gastrointestinal tract, dermatological and/or neurological), attributed to a postinfectious and atypical complication occurring weeks to months after infection with severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). The diagnosis is primarily based on findings encompassing persistent fever, elevated inflammatory markers, multiorgan involvement and a temporal relationship with COVID‐19 infection. The existing literature on MIS‐A, although growing, is limited to case reports and small case series. It is imperative that dermatologists be aware of this entity and aid the critical care team to ensure timely diagnosis and early therapeutic intervention. In this review, we concisely highlight the varied presentations, pathogenesis and treatment options in MIS‐A. Abstract : Multisystem inflammatory syndrome in adults (MIS‐A) is an inflammatory condition affecting multiple extrapulmonary organ systems (cardiac, gastrointestinal tract, dermatological and/or neurological), attributed to a post‐infectious and atypical complication occurring weeks to months after infection with SARS‐CoV‐2. The existing literature on MIS‐A, although growing, is limited to case reports and small cases series. It is imperative that dermatologists be aware of this entity and aid the critical care team to ensure timely diagnosis and early therapeutic intervention. In this review, we concisely highlight the varied presentations, pathogenesis and treatment options in MIS‐A. Click here for the corresponding questions to this CME article.